DE L’ÉCRITURE DE SOI À L’AUTOTHÉORIE : « LE FRIGIDAIRE EST VIDE. ON PEUT LE REMPLIR » DE CHANTAL AKERMAN - LAZAR, Andrei (Studia Universitatis Babeș-Bolyai Philologia, 2025)
From Self-Writing to Autotheory: “Le frigidaire est vide. On peut le remplir” by Chantal Akerman. Chantal Akerman’s work is characterised by her ability to merge different artistic forms such as cinema, writing and contemporary art installations. These allow her to question her own identity, her family heritage and her status as a filmmaker, in a creative freedom that reflects her opposition to generic conventions and affirms her openness to experimentation. “Le frigidaire est vide. On peut le remplir” is an autotheoretical work, as Lauren Fournier defines it, incorporating elements of feminism, intersectionality, and a reflection of concepts emerging from Barthes, Deleuze, Freud and Lacan. This transdisciplinary approach is doubled by an intermedial one, since this autobiographical narrative is revisited and modified as part of a contemporary art installation that also reiterates and questions the autotheoretical elements of her work. REZUMAT. De la scriitura autobiografică la autoteorie: „Le frigidaire est vide. On peut le remplir” de Chantal Akerman. Opera cineastei Chantal Akerman se caracterizează printr-o extraordinară capacitate de a îmbina diferite forme de exprimare artistică, precum filmul, scriitura și arta contemporană, care îi permit să-și pună sub semnul întrebării propria identitate, moștenirea familială și statutul de cineast, în spiritul libertății creatoare și a refuzului convențiilor generice, afirmându-și totodată și disponibilitatea față de experiment. Textul autobiografic „Le frigidaire est vide. On peut le remplir” poate fi considerat ca o formă de autoteorie, așa cum o definește Lauren Fournier, încorporând elemente de feminism și intersecționalitate, dar și concepte desprinse din teoriile lui Barthes, Deleuze, Freud și Lacan. Această abordare transdisciplinară este dublată de una intermedială, întrucât scriitura autobiografică devine material în sine pentru o serie de instalații de artă contemporană care pun permanent în discuție rolul și pertinența elementelor (auto)teoretice ale propriei opere. Cuvinte-cheie: scriere, auto-narațiune, feminism, literatură minoră, artă contemporană Article history: Received 15 December 2024; Revised 26 February 2025; Accepted 06 March 2025; Available online 25 March 2025; Available print 30 April 2025.